2018
DOI: 10.1016/j.envpol.2018.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of microplastics (MP) in wild mussels indicate that MP ingestion by humans is minimal compared to exposure via household fibres fallout during a meal

Abstract: Microplastics (MPs) are the most numerous debris reported in marine environments and assessment of the amounts of MPs that accumulate in wild organisms is necessary for risk assessment. Our objective was to assess MP contamination in mussels collected around the coast of Scotland (UK) to identify characteristics of MPs and to evaluate risk of human exposure to MPs via ingestion of mussels. We deployed caged mussels (Mytilus edulis) in an urbanised estuary (Edinburgh, UK) to assess seasonal changes in plastic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
284
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(304 citation statements)
references
References 54 publications
13
284
5
2
Order By: Relevance
“…For instance, Lefebvre et al (2019) found that only a small fraction of all debris ingested by sardines (2.3%) and anchovies (1.5%) could be identified as microplastic particles, results that are consistent with other studies also reporting that natural fibers dominate the composition of particles ingested (Remy et al 2015; Zhao et al 2016; Catarino et al 2018; Kroon et al 2018). Misidentification is not necessarily isolated to fibers but can also include spheres.…”
Section: Resultssupporting
confidence: 73%
“…For instance, Lefebvre et al (2019) found that only a small fraction of all debris ingested by sardines (2.3%) and anchovies (1.5%) could be identified as microplastic particles, results that are consistent with other studies also reporting that natural fibers dominate the composition of particles ingested (Remy et al 2015; Zhao et al 2016; Catarino et al 2018; Kroon et al 2018). Misidentification is not necessarily isolated to fibers but can also include spheres.…”
Section: Resultssupporting
confidence: 73%
“…Catarino et al () compared microplastic exposure from eating mussels to that acquired from indoor dust fallout during the meal. The authors concluded that the latter likely contributed orders of magnitude more microplastics than did the former, highlighting the importance of human exposure in the indoor environment.…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…Carbery et al (2018) reviewed that there is no robust evidence for the transfer of microplastics and associated contaminants from seafood to humans and the implications for human health. Microplastic uptake through seafood consumption may be minimal when compared to other routes of human exposure, for example, fibers settling on consumables, or dust in the household (Catarino et al 2018). Food items packaged in plastic may lead daily exposure to different plastic-associated chemicals up to 250 μg kg -1 body weight (EFSA 2011; Muncke 2011).…”
Section: Microplastics and Human Healthmentioning
confidence: 99%